Investigation of Ether-Based Ionic Liquid Electrolytes for Lithium-O2 Batteries. Issue 2 (1st January 2015) - Ferrari, S.; Quartarone, E.; Tomasi, C.; Bini, M.; Galinetto, P.; Fagnoni, M.; Mustarelli, P.
Abstract : In this work, we showed the results of the characterization of ether based electrolytes for Li-O2 batteries, prepared by mixing TEGDME and N -methoxyethyl- N -methylpyrrolidinium bis(trifluoromethanesulfonyl)-imide ionic liquid (IL). The mixtures having different ratio TEGDME/IL and containing LiCF3 SO3 salt, were thoroughly characterized by thermal analysis, conductivity and electrochemical stability measurements. Their potential use as electrolytes in Li-O2 batteries was checked investigating Li/TEGDME-IL/O2 cells by means of cycling voltammetry (CV) and galvanostatic charge-discharge tests.